2013
DOI: 10.1515/bnm-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles induce cytotoxicity, but not cell transformation or genotoxicity on Balb3T3 mouse fibroblasts

Abstract: Silver nanoparticles (Ag NPs) are one of the most common nanomaterials present in nanotechnologybased products. Here, the physical chemical properties of Ag NPs suspensions of 44 nm, 84 nm and 100 nm sizes synthesized in our laboratory were characterized. The NM-300 material (average size of 17 nm), supplied by the Joint Research Centre Nanomaterials Repository was also included in the present study. The Ag NPs potential cytotoxicity was tested on the Balb3T3 cell line by the Colony Forming Efficiency assay, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
4
4
Order By: Relevance
“…The effective concentration (10.60 μg/mL) of AgNPs in our study is comparable to that published by others (0.01-20.00 μg/mL). In contrast, Broggi et al [ 24 ] showed a negative impact of AgNPs on MN formation in the same cell line used in our study. In dispersion conditions without the use of a stabilizing agent, the diameter of AgNPs in our study was 80.0 ± 6.0 nm, which is smaller than that reported in the study by Broggi et al [ 24 ] (117.8 ± 16.6 nm).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The effective concentration (10.60 μg/mL) of AgNPs in our study is comparable to that published by others (0.01-20.00 μg/mL). In contrast, Broggi et al [ 24 ] showed a negative impact of AgNPs on MN formation in the same cell line used in our study. In dispersion conditions without the use of a stabilizing agent, the diameter of AgNPs in our study was 80.0 ± 6.0 nm, which is smaller than that reported in the study by Broggi et al [ 24 ] (117.8 ± 16.6 nm).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Broggi et al [ 24 ] showed a negative impact of AgNPs on MN formation in the same cell line used in our study. In dispersion conditions without the use of a stabilizing agent, the diameter of AgNPs in our study was 80.0 ± 6.0 nm, which is smaller than that reported in the study by Broggi et al [ 24 ] (117.8 ± 16.6 nm). In addition, the effective concentration (10.60 μg/mL) of AgNPs in our study was higher than the exposure concentration (0.11-1.08 μg/mL) of AgNPs reported by Broggi et al [ 24 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…for Chlamydomonas reinhardtii, 2,26 Lemna minor, 27 bacteria 28 and cells. 29 Effective toxic concentrations were obtained for diverse aquatic organisms (Daphnia magna, Lemna minor and Pseudokirchneriella subcapitata) and for terrestrial organisms like Arthrobacter globiformis and Eisenia andrei. 30,31 Depending on the test media composition and the sensitivity of the organisms, the effective concentrations of AgNPs and the most frequently used control AgNO 3 exhibit considerable differences which are shown for bacteria 30 and algae.…”
Section: Introductionmentioning
confidence: 99%